CORRELATION OF AGE WITH COVID-19 IGG ANTIBODIES TITRE IN THE ADULT POPULATION OF MALEGAON: A PROSPECTIVE OBSERVATIONAL STUDY - Bagmar, Kamlesh Popatlal; Motiwala, Dr. Farooq F.; Nimbhore, Dr. Vishal; Shukla, Dr. Swanand; Yadav, Dr. Subhash; Kanitkar, Dr. Madhuri (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction: The year 2019 was affected by Pneumonia caused by SARS Cov 2 virus. This major health challenge whole world is facing and IgG antibodies titre has been widely used to assist the diagnostic and prognostic value. Important aspect of aging is decline in immune function. As per the aging process there are changes at humoral and cellular immune responses leading to impaired immune response which in turn leads to risk of infectivity and decreased vaccine responses. The current study's objectives were to assess the SARS-COV-2 antibody titre in the adult urban Malegaon population and to look for a relationship between age and antibody titre. Methods: Individuals who were residing in densely populated Malegaon village where formerly COVID- 19 was declared as hot spot during first wave were included with total sample size of 2454 and their blood samples were collected to get IgG antibodies from 12 January 2022 to 18 January 2022. Results: In this study we found that when the age advances the % of antibody level doesn’t change significantly. In 2454 samples there observed non-significant difference in antibody % and age group (p>0.05) Conclusion: These findings suggest extensive studies are required to bring uniform guideline for developing the vaccine strategy as age and antibodies level remained the same.